Modelling the factors influencing the intention to purchase halal products among students in higher learning institutions using multiple linear regression / Shamsunarnie Mohamed Zukri ... [et al.] - Mohamed Zukri, Shamsunarnie; Hasnor, Hadi Zami; Juha Seman, Muhammad Hafizzullah; Abu Yazid, Hazman; Ibrahim, Nurul Bariyah; Mohd Fauzi, Noor Zafarina; Hamzah, Nor Hazreeni; Ibrahim, Nur Safwati (Unit Penerbitan, UiTM Kelantan, 2022)
In Arabic, the word halal means "permissible" or an obligation that regulates all aspects of Muslims' lives worldwide. Now, it appears that the definition of halal expands to the extent that virtually all goods and services including cosmetics, clothing, pharmaceuticals, financial services and even tour packages can obtain the status of halal. Halal product status in Malaysia is still vague which sometimes could lead to questionable halal status. Therefore, this study was conducted to determine the factors influencing university students' intention to purchase halal products in Kelantan. A cross-sectional design was conducted among all full-time undergraduate students from March until July 2020, at Universiti Teknologi MARA, Kota Bharu Campus in Kelantan. About 327 students were randomly selected by using Proportionate Stratified Random Sampling. A self-administrated structured questionnaire was used as a research tool in this study. The data was analyzed by performing multiple linear regression analysis. Of the five factors, attitude, subjective norm, perceived behavior control and religiosity significantly influenced the intention to purchase halal products among students. Only halal awareness was not significantly influenced. Attitude was found to be the most influential factor that influenced university students' intention to purchase halal products. This study's finding can be used as an ongoing framework to enhance more optimal findings to halal sectors in Malaysia especially for those who are directly involved in buying behavior of halal products.